Protocol for differentiating human pluripotent stem cells into midbrain organoids for targeted microinjection of viruses - Mengdan Tao; Qi Chen; WeiWei Gao; Shanshan Wu; Yan Liu (STAR Protocols)
Summary: Midbrain organoids serve as a valuable model for studying brain development and disease. Here, we present a viral infection protocol for midbrain organoid models. We describe steps for human pluripotent stem cell (hPSC) differentiation into midbrain organoids; equipment preparation; and targeted virus microinjection into organoids to reduce viral load, minimize cytotoxicity, and preserve structural integrity. We then detail procedures for visualizing infected cells. By combining the virus with specific promoters, this protocol enables precise targeting of tube-like ventricular zone (VZ) regions.For complete details on the use and execution of this protocol, please refer to Zhu et al.,1 Wu et al.,2 Xu et al.,3 and Lu et al.4 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.